Segmental osteotomy for the correction of a malpositioned single implant: an 8-year follow-up - Cunha, Hiron Andreazza da; Nary Filho, Hugo; Batista, José Gilmar; Matsumoto, Mariza Akemi [UNESP] (My University, 2011)
This case report is an 8-year follow-up of a malpositioned single implant, which was treated with segmental osteotomy, to confirm the treatment's characteristics, indications, and advantages. Deep buccal positioning of an endosseous implant placed in the maxillary left central incisor area did not permit acceptable prosthetic rehabilitation, despite its favorable bone insertion with no significant marginal bone loss. The surgical procedure included osteotomy and block movement performed toward the lingual and cervical position, fixed with a provisional prosthesis and miniplates and mini-implants. A connective tissue graft was necessary for esthetics optimization and was performed in a second stage. Advantages including the prevention of alveolar ridge damage, the improvement of gingival contour, and the use of an already integrated implant are presented. Clinically satisfactory hard and soft tissue stability permitted us to consider segmental surgery as a reliable alternative for malpositioned osseointegrated implants.
Keywords: Dental implants; Malpositioned implant; Prosthetic rehabilitation; Segmental osteotomy